Studies on the antioxidant properties of selected Malaysia "ULAMS" - Alias, Nur Nadzifah Che (2005)
The antioxidant activity of some edible Malaysian ulams found in Kelantan, Malaysia, was studied. The ulams studied were Oroxylum indicum (Beka), Apium graveo/ens (Sup/Sadri), and Vitex negundo (Lemuni). Percent recovery of the prepared ulam extracts was ranged from 2.47 to 2.54%. the methanolic extracts of the ulams at 0.2 mg/ml concentration level was tested using the autoxidation of lipid assay in a water-alcohol system, 0.40 mg/ml for DPPH radical scavenging assay and 2.50 g/ml for xanthine/xanthine oxidase (X/XOD) superoxide scavenging test. For the autoxidation of lipid (ML) assay in a water-alcohol system, 2, 6-di-tertbutylhydroxytoluene (BHT), a synthetic antioxidant, was used as standard antioxidant. It was found that both Oroxylum indicum (Beka) and Vitex negundo (Lemuni) possessed high antioxidant activity (92.9% and 92.9% for xanthine/xanthine oxidase superoxide scavenging test and 98.4% and 98.6% for DPPH radical scavenging assay, respectively). The decreasing order of antioxidant activity for inhibition of lipid autoxidation was observed as Vitex negundo (Lemuni) > Oroxylum indicum (Beka) > Apium graveolens (Sup/Sadri). Though all the test system did not yield the identical order of antioxidant activity but there was a similarity. However, irrespective of the type of the test carried out, the antioxidant activity of Vitex negundo (Lemuni) was found appreciably high. Therefore, it is worth to study further with the ulams for the present study, especially with Vitex negundo (Lemuni) and the outcome of the study can be of importance in dietary control of diseases.